Outer order, inner calm : declutter & organize to make more room for happiness - Rubin, Gretchen (Harmony Books, 2019)
"With clarity and humor, bestselling author of The Four Tendencies and The Happiness Project Gretchen Rubin illuminates one of her key realizations about happiness: For most of us, outer order contributes to inner calm. And for most of us, a rigid, one-size-fits-all solution doesn't work. In this easy-to-read but hard-to-put-down book, Gretchen Rubin suggests more than 150 short, concrete clutter-clearing ideas so each reader can choose the ones that resonate most. The fact is, when we tailor our approach to suit our own particular challenges and habits, we're far more likely to be able to create the order that will make our lives happier, healthier, more productive, and more creative. In the context of a happy life, a messy desk or crowded coat closet is a trivial problem--yet Gretchen Rubin has found that getting control of our stuff makes us feel more in control of our lives. By getting rid of things we don't use, don't need, or don't love, as well as things that don't work, don't fit, or don't suit, we free our mind (and our shelves) for what we truly value. In this trim book filled with insights, strategies, and sometimes surprising tips, Gretchen tackles the key challenges of creating outer order, by explaining how to "Make Choices," "Create Order," "Know Yourself--and Others," "Cultivate Helpful Habits," and, of course, "Add Beauty." At home, at work, and in life, when we get our possessions under control we feel both calmer and more energetic. With a sense of fun, and also a clear idea of what's realistic for most people, Gretchen Rubin suggests dozens of manageable steps for creating a more serene, orderly environment--one that helps us to create the lives we yearn for"--